Boundary Spanning PR of the Ministry of Health Through Community Engagement in Promoting a Healthy Lifestyle at the Event "Ayo Sehat Fest 2023" - Ruvira Arindita; Dandy Rayhan Kharisma (ULTIMA Comm, 2024)
Boundary Spanning is defined as a function in the interaction between an organization and its environment. One of the steps taken by the Ministry of Health to promote the transformation of the health system is by involving the community through a special event, "Ayo Sehat Fest 2023." This study aims to understand how boundary spanning is carried out by the Ministry of Health through community engagement to promote a healthy lifestyle in society. It adopts a constructivist paradigm and a qualitative approach with a descriptive nature. The informants in this study are Ministry of Health employees involved in the "Ayo Sehat Fest 2023" event. The research findings show that the boundary spanning efforts carried out as a government public relations activity are divided into three parts: pre-event, during the event, and post-event. Additionally, community engagement is applied using three dimensions. First, the content dimension is reflected in the consistency of the message or information delivered, which is factual regarding health. Second, the source dimension is reflected in the messages delivered for health promotion, involving communities with expertise in the field. Third, openness and transparency are practiced by the Ministry of Health with its community as part of the process dimension